2 - Negotiating the Use of Native Languages in Emerging Pluralistic and Independent Broadcast Systems in Africa - Isaac Abeku Blankson (Africa Media Review, 2005)
Since the 1990s liberal and democratic reforms in African countries, competitive independent and pluralistic broad castings, particularly radio, have emerged to provide channel and program diversity for the first time in these emerging democracies. Independent radio has become an entrée into civic discourse and socio-political awareness and a force for social and political integration and accountability. However, these positive developments have overshadowed the observation that Africa’s emerging independent radio has become an avenue for corroding their societies’ languages and cultures. While they have been insensitive to native languages, they are successful in domesticating the languages of their former European colonizers. Using the experiences of Ghana’s radio, this article raises important questions about the relationship between Africa’s native languages and the development of a true African broadcasting system. It calls for a re-examination of the belief that the multilingual character of African societies does not serve broadcasting well. It argues that a true African broadcast system that allows for mass participation can develop only if African broadcasters and policy makers address the native language deficiency in broadcasting. Finally, it calls for a deliberate and planned effort to promote the use of African native languages over Euro-imperial languages in broadcasting.